Suspending Hasty Legitimation: Affirming The Substance of Living Hadith as A Study of Reception of Text and Practice - Fahmi Riady; Hairul Hudaya; Abdul Karim (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Living hadis studies have shifted the focus of hadith scholarship from textual work to the reading of socio-religious practices. This shift is important because hadith is not only present as reports preserved in books, but also moves through traditions, rituals, communal actions, religious authority, digital media, and the collective memory of Muslim communities. However, the expansion of this field has generated conceptual and methodological problems. In several studies, the term living hadis is used too loosely to name religious practices without adequately explaining the relationship between hadith texts, transmission agents, social practices, and practitioners’ meanings. This article addresses three main issues: conceptual problems in the use of the term living hadis; distinctions between living hadis, living sunnah, living fiqh, living Qur’an or Qur’anic practices, sīrah–Maulid–Prophetic praise traditions, and local Islamic traditions; and a methodological model for examining the relationship between texts, practices, transmission agents, and social reception. Through a critical literature review and conceptual analysis, the article shows that an analytical category should be determined by the dominant object of reception and source of authority, rather than solely by the label used in previous studies. Living hadis is therefore more appropriately positioned as a study of hadith reception, rather than as normative legitimation of tradition. Its analysis proceeds through the identification of social practices, examination of hadith claims, textual validation, mapping of transmission agents, analysis of social reception, practical transformation, and category evaluation. This framework keeps living hadis within the field of hadith studies without losing its social sensitivity.